Standardisation versus adaptation in international marketing of Polish companies operating in foreign markets: The case of Maspex - Paweł Milka; Jakub Garncarz (International Entrepreneurship Review)
Objective: The article examines the application of standardisation, adaptation, and glocalisation strategies in international marketing, with Maspex Group serving as a case study. It analyses how Polish firms, exemplified by Maspex, navigate the challenges of foreign market expansion through these strategic approaches and evaluates their implications for organisational performance and brand perception.